Co(ii)-based metal–organic framework induces apoptosis through activating the HIF-1α/BNIP3 signaling pathway in microglial cells. Issue 10 (16th September 2021) - Yan, Xueting; Yang, Qundi; Fang, Xiaolong; Xiong, Ping; Liu, Shuang; Cao, Zhengyu; Liao, Chunyang; Liu, Sijin; Jiang, Guibin
Abstract : The neurotoxicity induced by Co(ii )-based MOFs provides new insights into understanding the environmental health and safety impacts of MOFs. Abstract : Metal–organic frameworks (MOFs) are an emerging class of porous hybrid materials constructed by coordination of metal clusters with organic ligands, and have attracted tremendous attention due to their superior properties. Although nanoscaled MOFs have been increasingly developed for bioapplications, little is known about their toxicity and potential health risks. In this study, we demonstrated that a typical cobalt-based MOF (ZIF-67) induced apoptosis in microglial cells, through activating the hypoxia-inducible factor-1α (HIF-1α)/BCL-2 19-kDa interacting protein 3 (BNIP3) signaling pathway. Combined cellular assays and transcriptomic analysis confirmed that ZIF-67 was able to imitate hypoxia in vitro, induced the generation of reactive oxygen species (ROS), enhanced the expression of HIF-1α and BNIP3, and eventually led to apoptosis. The inflammatory process and element dyshomeostasis in microglial cells also appeared to be associated with ZIF-67 exposure. The released Co 2+ from ZIF-67 could not solely explain the specific neurotoxicity of ZIF-67, since ZIF-67 generally exhibited higher toxicity than commensurable Co 2+ . The neurotoxicity of ZIF-67 and its underlying mechanism were further verified in vivo . These results provided not only mechanistic insights into the neurotoxicity of ZIF-67, i.e., ROS-induced apoptosis through activating the HIF-1α/BNIP3 signaling pathway, but also comprehensive data, such as oxidative stress, homeostasis, and gene transcription, for environmental risk assessment of MOFs' impact on organisms.